Applying pharmacokinetic/pharmacodynamic principles in critically ill patients: optimizing efficacy and reducing resistance development - Abdul Aziz, Mohd. Hafiz; Lipman, Jeffrey; Mouton, Johan W.; Hope, William W.; Roberts, Jason A. (Thieme Medical Publishers, 2015)
The recent surge in multidrug-resistant pathogens combined with the diminishing antibiotic pipeline has created a growing need to optimize the use of our existing antibiotic armamentarium, particularly in the management of intensive care unit (ICU) patients. Optimal and timely pharmacokinetic/pharmacodynamic (PK/PD) target attainment has been associated with an increased likelihood of clinical andmicrobiological success in critically ill patients. Emerging data, mostly from in vitro and in vivo studies, suggest that optimization of antibiotic therapy should not only aim to maximize clinical outcomes but also to include the suppression of resistance. The development of antibiotic dosing regimens that adheres to the PK/PD principles may prolong the clinical lifespan of our existing antibiotics by minimizing the emergence of resistance. This article summarizes the relevance of PK/PD characteristics of different antibiotic classes on the development of antibiotic resistance. On the basis of the available data, we propose dosing recommendations that can be adopted in the clinical setting, to maximize therapeutic success and limit the emergence of resistance in the ICU.